Diseño de vivienda para afrontar una pandemia (2020)
In the present work we will talk about a proposal for a single-family house designed in order to face possible pandemics such as the one we are currently experiencing, the following points will be developed: hygiene, recreation, coexistence, isolation, selfsustainability and finally reuse of water resources. Architecturally, the solution to the problems presented in each of the aforementioned points was sought by analyzing multiple materials and social behaviors, and in this way to be clear about the characteristics and behaviors to take into account for the design of single-family houses, designed with in order for tenants to overcome future pandemics in a comfortable and healthy way.